Absurd, prowokacja, skandal, czyli determinanty współczesnego sukcesu politycznego na przykładzie aktywności politycznej Janusza Korwina-Mikkego (Świat Idei i Polityki, 2014)
The article discusses the phenomenon of controversy on the political scene and depicts Janusz Korwin-Mikke as the leader of the mentioned issue. The purpose of the article was not a substantive assessment attempt, but only the location of the phenomenon in a political context. The paper is testing a definition of such phenomena as scandal, absurd, or provocation in the light of the political reality. An important part of the article is also a section on ethics in politics and its new dimension. In the text, we find a short biography of Janusz Korwin-Mikke, presentation of his political views. We also find a reference to the media and their impact on the world of politics.